Observation of e(+)e(-) annihilation into the C=+1 hadronic final states rho(0)rho(0) and phi rho(0) - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We report the first observation of e+e- annihilation into states of positive C parity, namely, ρ0ρ0 and ρ0. The two states are observed in the π+π-π+π- and K+K-π+π- final states, respectively, in a data sample of 225fb-1 collected by the BABAR experiment at the Positron-Electron Project II e+e- storage rings at energies near s=10.58GeV. The distributions of cos θ*, where θ* is the center-of-mass polar angle of the meson or the forward ρ0 meson, suggest production by two-virtual-photon annihilation. We measure cross sections within the range |cos θ*|<0.8 of σ(e+e-→ρ0ρ0)=20.7±0.7(stat) ±2.7(syst)fb and σ(e+e-→ρ0)=5.7±0.5(stat)±0. 8(syst)fb. © 2006 The American Physical Society.